Peripheral Blood Eosinophilia and Hypersensitivity Reactions among Patients Receiving Outpatient Parenteral Antibiotics - Blumenthal, Kimberly G. (J Allergy Clin Immunol, 2015)
BACKGROUND: While drug-induced peripheral eosinophilia complicates antimicrobial therapy, little is known about its frequency and implications. OBJECTIVE: We aimed to determine the frequency and predictors of antibiotic-induced eosinophilia and subsequent hypersensitivity reactions (HSRs). METHODS: We evaluated a prospective cohort of former inpatients receiving intravenous antibiotic therapy as outpatients with at least one differential blood count. We used multivariate Cox proportional hazards models, with time-varying antibiotic treatment indicators, to assess the impact of demographic data and antibiotic exposures on eosinophilia and subsequent HSR, including documented rash, renal injury, and liver injury. Possible Drug Rash Eosinophilia and Systemic Symptoms (DRESS) syndrome cases were identified and manually validated. RESULTS: Of 824 patients (60% male, median age 60 years, median therapy duration 41 days), 210 (25%) developed eosinophilia with median peak absolute eosinophil count of 726/mL [IQR: 594–990/mL]. Use of vancomycin, penicillin, rifampin, and linezolid were associated with a higher hazard of developing eosinophilia. There was subsequent HSR in 64/210 (30%) patients with eosinophilia, including rash (N=32), renal injury (N=31), and liver injury (N=13). Patients with eosinophilia were significantly more likely to develop rash (HR = 4.16 [2.54, 6.83]; p<0.0001) and renal injury (HR = 2.13 [1.36, 3.33]; p=0.0009), but not liver injury (HR = 1.75 [0.92, 3.33]; p=0.09). Possible DRESS syndrome occurred in 7/824 (0.8%) patients; 4 (57%) were on vancomycin. CONCLUSIONS: Drug-induced eosinophilia is common with parenteral antibiotics. While most patients with eosinophilia do not develop an HSR, eosinophilia increases the hazard rate of developing rash and renal injury. DRESS syndrome was more common than previously described.